Permanent effects of economic crises on household welfare: estimations from Argentina's downturns - Cruces, Guillermo Antonio (2010)
This study estimates the relationship between GDP growth and severe crises on poverty, youth unemployment, and a series of human capital related outcomes, such as infant and maternal health, and school enrollment and progression. The identification strategy relies on provincial variation in GDP, and on a difference in differences estimation from the severe 1999-2002 crisis. Besides the expected and well-documented relationship between crises and poverty levels, the main finding of this study is a strong effect on infant mortality and low weight at birth.